Open Social System: The Problem of The Impact of Vertical Social Mobility on The Prospects for Economic Growth (In the Context of The Discussion About the Affirmative Action Prospects) - KOLIN, YURI V. (The journal of contemporary issues in business and government, 2021)
In this article for the first time are considered the aspects of positive discrimination state politics in the context of its impact on the processes of social integration, vertical social mobility and economic growth rate. The comparative analysis of positive discrimination models in USSR and Western countries has been carried out. The repercussions of the Russia’s abandonment of the positive discrimination politics are distinguished. The actuality of the analysis of the forms of vertical social mobility stimulation is based on their potential impact on economic growth in the conditions of high social inequality and the growing tendency to global social polarization. The high level of social inequality is a barrier to upward mobility, the expansion of economic activity and the dynamic economic growth. The article justifies the importance of the open social system as a transparent system of social elevators for economic growth’ acceleration and states the correlation between the level of vertical social mobility and the economic growth in long-term perspective. The methodology of the research is based on the complex approach to the problem of vertical social mobility and the use of the models of positive discrimination, and the comparative analysis of the Soviet and Western practice of its applying is carried out. The article is based on the research of the processes of vertical social mobility and social inequality rate codependence in the context of understanding of social inequality rate as a social and economic development prospects’ indicator. The modern Russian scholars view the problem of positive discrimination in the predominantly negative light: as a Soviet legacy, within the paradigm of understanding the Soviet society as totalitarian. Whereas in Western society the use of positive discrimination models is widely studied as a factor of lowering the social inequality and strengthening the social integration within the separate social spheres: politics, industry, education, gender and race relations. The article for the first time names the problem of national importance of positive discrimination as a factor of increasing the social system openness and the acceleration of economic growth in long- term perspective. The research can be considered as a review of the examples of the positive discrimination models usage and the invitation to further discussion on the perspectives of wider applying of the positive discrimination models as an indirect factor of strengthening the social integration and economic growth stimulation.